The Effect of Supporting the Educational System on Pregnant Mother's Preeclampsia in The Hospital. Auras Of Self-Aggressiveness. - Isnaeni, Ely; Wahyu Nur Pratiwi; Sheylla Septina Margareta; Wahyu Sri Astutik; Sujatmiko (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Background Aki (Mother Death Number) and Aki (Baby Death Number) are caused by pre-eclampsia. In 2021, there were 76,000 women and 500,000 babies die due to pre eclampsia.Based on the prevalence of such events then one of the interventions to reduce AKI and AKB is given a supportive educational system by providing education such as teaching, guidance and guidance, Such interventions can enhance knowledge in the attitude toward preeclampsia. The goal is to find out if there's an educational system effect on a pregnant mother's pre eclampsia at the hospital. Aura syifa self. This method of research is a categorical study with pre-perimental research designs and research methods of one group pre test and post-test. Sampling techniques use accidental technique so that they get 25 responders. Willcoxon test analysis shows a self-care supportive educational system effect on maternity pre eclamation with 0.000 significance in which < (= 0.05 ). Conclusion, studies have proved to have an effect on the immune system on the preeclampsia of the hospital's euras of self - euphemism. Suggest the next researcher is able to add common data regarding attitudes like factors that affect attitudes (personal experiences), the influence of others considered important and cultural influence)